2018
DOI: 10.5194/amt-2018-67
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development of time-varying global gridded Ts-Tm model for precise GPS-PWV retrieval

Abstract: Water-vapor-weighted mean temperature, Tm, is the key variable to estimate mapping factor between GPS zenith wet delay (ZWD) and precipitable water vapor (PWV). In near real-time GPS-PWV retrieving, estimating Tm from surface air 10 temperature Ts is a widely used method because of its high temporal resolution and a fair degree of accuracy. Based on the Tm estimates and the extracted Ts parameters at each reanalysis grid node, analyses of the relationship between Tm and Ts were performed without smoothing of d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…An example is the ECMWF Re-Analysis-Interim (ERA-Interim) dataset, which is a modern reanalysis product produced by the ECMWF using the assimilation system. The majority of the data used to produce ERA-Interim are from satellites, although radiosonde data have also been assimilated into it [28,35]. However, a test at 20 GNSS sites showed that the root-mean-square error between the surface temperature calculated by ERA-Interim and the measured surface temperature reached 2.0 K, while another test at 20 radiosonde stations showed that the relative error of T m calculated from ERA-Interim compared with T m calculated by radiosonde data reached 0.5% [36].…”
Section: T M Determined By the Numerical Integration Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…An example is the ECMWF Re-Analysis-Interim (ERA-Interim) dataset, which is a modern reanalysis product produced by the ECMWF using the assimilation system. The majority of the data used to produce ERA-Interim are from satellites, although radiosonde data have also been assimilated into it [28,35]. However, a test at 20 GNSS sites showed that the root-mean-square error between the surface temperature calculated by ERA-Interim and the measured surface temperature reached 2.0 K, while another test at 20 radiosonde stations showed that the relative error of T m calculated from ERA-Interim compared with T m calculated by radiosonde data reached 0.5% [36].…”
Section: T M Determined By the Numerical Integration Methodsmentioning
confidence: 99%
“…Bevis et al [19] first specified the formula for calculating T m as T m = 70.2 + 0.72 • T s with 8718 radiosonde profiles of 13 stations distributed in North America. However, it was found that the coefficients of the Bevis formula vary with the geographical location and season [27][28][29], so it is necessary to estimate the coefficients through measurements in a specific region and period of time. Li et al [29] established regional T m models for the Hunan region, China, including models with one meteorological factor (T m -T s ), two mete-orological factors (T m -T s , e s ) and three meteorological factors (T m -T s , e s , P s ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2019) is adopted to calculate the Tm. The authors verified its prominent advantages over other global models, such as Bevis and GPT2w (Jiang et al., 2019). In the present study, Tm_ERA5 model , Tm_FNL model , and Tm_GFS model represent the schemes of calculating Tm from the TsTm model using surface temperature data provided by the ERA5, FNL, and GFS, respectively.…”
Section: Resultsmentioning
confidence: 87%
“…For the second approach, the time‐varying global gridded TsTm model developed by Jiang et al. (2019) is adopted to calculate the Tm. The authors verified its prominent advantages over other global models, such as Bevis and GPT2w (Jiang et al., 2019).…”
Section: Resultsmentioning
confidence: 92%